2019
DOI: 10.1002/hep4.1427
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of SMAD‐Specific E3 Ubiquitin Protein Ligase 1 in Alcoholic Steatohepatitis in Mice

Abstract: Excessive accumulation of lipids in the liver is crucial in the pathogenesis of alcoholic steatohepatitis and may be partly mediated by impaired degradation of lipid droplets by autophagy. The E3 ubiquitin ligase SMAD‐specific E3 ubiquitin protein ligase 1 (SMURF1) regulates selective autophagy by ubiquitinating proteins on cargo destined for autophagic delivery to the lysosome for degradation. Here, we evaluated the role of SMURF1 in the regulation of hepatic lipid degradation in alcoholic steatohepatitis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…62 In the C26 model, a functional test confirmed an increased hepatic protein synthesis. 63 In addition, we observed a reduction in the expression of Atg7 (L2FC: À0.53, q-value <0.001), a key regulator of autophagy, 64 and Smurf1 (L2FC: À0.42, qvalue <0.001), an important E3 ubiquitin protein ligase in the liver, 65 suggesting a reduction in protein degradation for nitrogen sparing. Atg7 was also decreased in another preclinical model of cachexia (LLC model) in which the authors reported a decrease in autophagy machinery with cancer progression.…”
Section: Amino Acids Are Captured By the Liver Of Cachectic Mice Main...mentioning
confidence: 87%
“…62 In the C26 model, a functional test confirmed an increased hepatic protein synthesis. 63 In addition, we observed a reduction in the expression of Atg7 (L2FC: À0.53, q-value <0.001), a key regulator of autophagy, 64 and Smurf1 (L2FC: À0.42, qvalue <0.001), an important E3 ubiquitin protein ligase in the liver, 65 suggesting a reduction in protein degradation for nitrogen sparing. Atg7 was also decreased in another preclinical model of cachexia (LLC model) in which the authors reported a decrease in autophagy machinery with cancer progression.…”
Section: Amino Acids Are Captured By the Liver Of Cachectic Mice Main...mentioning
confidence: 87%
“…However, an LD-associated E3 ligase that cooperates with these factors and substrates for this putative degradation pathway has yet to be identified. AIP4/5, which are recruited to LDs by spartin (Eastman et al 2009, Edwards et al 2009, Hooper et al 2010, Tokunaga et al 2013, and SMURF1 (Petrasek et al 2019) have been proposed to function as LD-associated E3 ligases. These proteins have not been observed in most proteomic analyses of LD fractions, although their association may be lost during the biochemical isolation of LDs or be limited to specific cell types.…”
Section: Lipid Droplet-associated Degradationmentioning
confidence: 99%
“…Promotes ubiquitination and subsequent proteasome degradation of MAVS [33]. SMURF1 regulates selective autophagy by ubiquitinating proteins used for autophagy delivery to cargo for lysosomal degradation [34]. ITGA3 is an integrin subunit alpha 3 receptor for fibronectin, laminin, collagen, epiligrin, thrombospondin and CSPG4, it provides a dock site for FAP (seprase) in the invading pseudopod plasma membrane in a collagen-dependent manner, and therefore may participate in the process of adhesion, formation of invasive pseudopod and stroma degradation to promote cell invasion.…”
Section: Discussionmentioning
confidence: 99%